Evaluasi Pembelajaran PKN di MIS TPI Sumber Rejo - Abdulgani Jamora Nasution; Tania Amara Br Pakpahan; Nabila Putri Andini; Isma Nurkhafifah BR BB (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2023)
Assessment is essentially a process of making decisions about the success of students, whether students are declared successful or fail in mastering a particular skill. Assessment and evaluation have similarities and differences. The similarity is that both have the meaning of assessing or determining the value of something. The difference is that assessment is used in a narrower context and is usually carried out internally, for example, like a teacher assessing student learning outcomes. The research method used in this study is a qualitative method. Qualitative method is a type of research that aims to comprehensively understand the phenomena experienced by the object of research, such as behavior, perceptions, motivations, actions, etc., through a special natural context. through specific natural contexts, and descriptions in scientific language and methods. This research results that first, is where the learning evaluation must be well planned, namely by determining and conveying the time for carrying out the learning evaluation. Second, the implementation of learning evaluation which is the execution step of the evaluation plan that was previously made. And, the last is the third stage which is no less important, whereas this is rarely carried out by other teachers in general, namely the analysis of the results of the PKN learning evaluation. Keywords: Evaluation, Learning, PKN